Metallurgical and mechanical properties of failed railway screw coupling in screw part - Sabry.M. Abdel Aziz; F. Abdel Mouez; M.A. Morsy (Journal of Alloys and Metallurgical Systems)
Metallurgical and mechanical investigations were applied to investigate the failure of the screw in train screw coupling. The results showed that the steel of the screw parts is DIN 41Cr4 steel with ferrite-pearlite microstructure. This indicates that the steel did not have the proper heat treatment according to the UIC code (826, 3rd edition, 2004), which is hardening and tempering to give the best mechanical properties especially fatigue resistance. Moreover, SEM micrographs show that the initiation point of crack is at the sharp points of the thread root, these sharp points act as a stress raiser that initiates the crack and accelerates the fatigue failure. Proper hardening and tempering process was conducted; this gave tempered martensite microstructure with acceptable mechanical properties that agreed with UIC code 826. The tempered martensite structure has a high fatigue resistance than the ferrite-pearlite structure. Therefore, it is highly recommended to form the threads by rolling dies instead of machining. This will result in the formation of rounded thread roots instead of sharp thread roots. The rounded thread roots are expected to improve the fatigue resistance especially when it is always done after heat treatment processes.